Forests, Fairness, Finance: CIFOR-ICRAF’s vision for global climate action at COP29 in Baku - CIFOR-ICRAF (CIFOR-ICRAF, 2024)
The 2024 Forest Declaration Assessment recently showed that, despite global commitments to halt and reverse deforestation by 2030, progress remains alarmingly insufficient. Last year, deforestation and forest degradation continued at the same levels, or even worsened in some places, with primary forests facing significant destruction. Forest fires, exacerbated by human-induced climate change and land clearing, are growing in intensity and frequency, further undermining forest conservation efforts. Meanwhile, over 1 million hectares of tree cover was lost in 2023 in forested Key Biodiversity Areas, internationally recognized as critical for endangered species. Without a transformation of economic models and a global commitment to prioritize forest conservation, the world’s 2030 forest goals will remain out of reach.